Development of a web-based ground station system for an advanced nano-satellite (VELOX-I) - Goh, Wei Rong. (2013)
The replacement or migration of software-based applications to Web-based applications is a growing trend as it allows higher cross platform compatibility, ease of data consolidation and system management, efficient system updates and maintenance, and fewer requirements at end users.